Effect of magnetic field on thermal instability of Oldroydian viscoelastic rotating fluid in porous medium - Thakur, R.C.; Rana, G.C. (Zielona Góra: Uniwersytet Zielonogórski)
In this paper, we investigate the effect of a vertical magnetic field on thermal instability of an Oldroydian visco-elastic rotating fluid in a porous medium. By applying the normal mode analysis method, the dispersion relation governing the effects of rotation, magnetic field and medium permeability is derived and solved analytically and numerically.
Keywords: magnetic field; Oldroydian visco-elastic fluid; porous medium; rotation; thermal instability